PENGARUH KARAKTERISTIK DEWAN KOMISARIS TERHADAP KEPUTUSAN INVESTASI PERUSAHAAN NON-KEUANGAN PADA JAKARTA ISLAMIC INDEX 70 PERIODE 2020–2023 - Adli Rikanda Saputra (CV. Denasya Smart Publisher, 2026)
This study examines the effect of board of commissioners’ characteristics on investment decisions among non-financial firms listed in the Jakarta Islamic Index 70 (JII70) during the 2020–2023 period. Investment decisions are proxied by the investment-to-asset ratio, which reflects firms’ long-term capital allocation intensity. The study employs secondary data obtained from annual reports and corporate governance reports, covering 25 firms and generating 100 panel observations. Panel data regression is applied, and model selection tests indicate that the Fixed Effect Model is the most appropriate specification. The results reveal that board independence has a positive and significant effect on investment decisions, while board size has a negative and significant effect. In contrast, board gender diversity does not have a significant impact on firms’ investment decisions during the study period. These findings suggest that monitoring effectiveness and board structure efficiency play a more prominent role in shaping investment intensity than gender composition on the board. This study contributes to the Islamic corporate governance literature by providing empirical evidence from Indonesia’s JII70 on how board independence and board structure efficiency are associated with firms’ investment intensity.